LITERATURE REVIEW THE RELATIONSHIP BETWEEN TRANSPORT DRIVERS AND HYPERTENSION INCIDENTS - Runtu, Lorien Grace; Bentian, Eiren Beradri (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
ntroduction : Work as a transport driver is one of the jobs that are at risk of developing hypertension. In transport drivers hypertension is one of the risk factors that cause accidents in transport drivers. Purpose: This study was to analyze articles related to the work of transport drivers with the incidence of hypertension. Methods: research using this type of researchliterature review namely a research in the form of a reviewliterature review using the results of previous research and textbooks or research journals. To obtain data that is in accordance with the research topic, a search for national and international-based journals is carried out in two databases, namelyScience Direct andGoogle Scholar by using the keywords increased blood pressure, transport drivers, high blood pressure. Researchers got 8 journals that match the title of the researcher, the results of the 8 journals found that there was a relationship between the work of transport drivers and the incidence of hypertension.Conclusion: From the results of a literature review search of a total of 8 journals, it was found that there was a relationship between the work of transport drivers and the incidence of hypertension